Intra-individual variance of bilateral femoro-tibial leg rotation: a CT study of 105 healthy subjects - Ries, Christian; Boese, Christoph Kolja; Ott, Nadine; Doerner, Jonas; Müller, Lars Peter; Hackl, Michael (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2021)
Purpose In cases of suspected rotational deformity of the lower limb, in particular in post-traumatic malalignment following closed nailing, there is a lack of adequate reference values. Available publications on leg rotation have either small sample sizes or do not include bilateral or whole leg rotation of healthy legs. This study aimed to determine side-specific reference values of lower limb rotation in a large healthy sample. This may be helpful in acute clinical settings as well as for medical expert opinion. Methods 226 consecutive bilateral lower limb computed tomography (CT) angiographies were screened. 105 patients (210 legs) were included (40 females, 65 males, mean age 67 ± 12 years). Bilateral axial femoral and tibial rotation alignment were independently measured and overall leg rotation was computed by two methods. Distributions, sex, and side differences were analyzed. Results Two-sided paired t tests showed significant differences between right and left for all measurements. The left side showed a more pronounced mean anteversion in the femur of 2.2° ( p = 0.002) and the right side higher mean external rotation in the tibia of 2.8° ( p < 0.001). Overall leg rotation showed 5.1° more mean external rotation on the right side ( p < 0.001) with both methods. Absolute side-to-side whole leg rotation difference was 9.5°. Absolute differences between both methods were 3.3°. The variance was high. 23 femora were retroverted, 1 tibia internally rotated, and 9 legs were overall internally rotated. No variables differed between female and male subjects except for femoral version (right p = 0.003 and left p = 0.002). Correlation coefficients were high (rho 0.550–0.934, all p < 0.001). Conclusion There is a significant prevalence of side-to-side asymmetry in femoro-tibial torsion. Although side-to-side differences are not extraordinary, comparative axial femoro-tibial rotation alignment should always be interpreted with caution. Level of evidence Diagnostic, retrospective cohort study, level III.